POWER POLITICS IN THE QURá¾¹N: HIZBUT TAHRIR INDONESIA AND THE CONCEPT OF CALIPHATE IN AL-WA'IE BY ROKHMAT S. LABIB - Sareh, Nurkholis; Nawawi, Abdul Muid (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
Power politics is a sovereign entity that aims to protect the interests of individuals and groups. The disharmony of Islamic politics triggered by stigma, discrimination, and persecution of the authorities against the people causes radicalism and intolerance of the concept of the state. Hizbut Tahrir, with textual interpretation dominatingly intervened by ideological reasoning, produced controversial sectarian revivalist thoughts, far from the universal message of the verse and its maqÄá¹£idÄ« meaning. This study examines the concept of power politics in the Quran through the theological analysis of the khilÄfah in al-Wa'ie. The method used in this study includes a descriptive-qualitative analysis of mauá¸Å«'Ä« interpretation through a context and content approach. This study concludes that the power politics of scripturalist, textualist, and fundamentalist interpretations in al-Wa'ie is far from authoritative (mu'tabar) scholars' thoughts or interpreted by jumping to conclusions, such as in solving al-Baqarah [2]: 30, al-NisÄ' [4]: â€‹â€‹59, and al-MÄ'idah [5]: 49. The verses of the power politics clearly state that the khilÄfah is an institution of civilization within state sovereignty, not a political conception that is taken for granted that negates Islam or a modern Islamic government system that substantially contains the principles of siyÄsah and maqÄá¹£id al-syÄri'ah.